1990
DOI: 10.1039/dt9900001687
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic characterization of the polyoxotungstate [Eu3(H2O)3(SbW9O33)(W5O18)3]18? and energy transfer in its crystalline lattices

Abstract: The potassium salt of the new mixed-polyoxotungstate anion [ Eu3( H, O), (SbW, O, ) (W50,&]l8-(1) has been prepared from WO, , Sb, O, , Eu(N0,),*6H20, and KOH in water and isolated in crystalline form as K, , H, [ Eu, ( H, O), (SbW, O, ) (W,O,,),]*25.5 H, O. It crystallizes in the monoclinic space group C2/m, with a = 30.250(7), b = 18.568(5& c = 22.101 (6) A, p = 109.19(8)", and, core is co-ordinated by a B-type a-SbWgO, unit and three W,018 units with tetrahedral conformation. Each Eu3+ in the core exhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
70
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 32 publications
2
70
0
Order By: Relevance
“…[8] Lanthanide-containing polyoxometalates constitute a type of compound of great impact. [9] Structural studies of lanthanide polyoxotungstates have been investigated and a number of compounds, for example Na 6 H 2 [Ce(W 5 O 18 ) 2 ]· 30H 2 O, [10] K 16 [Ce(P 2 W 17 O 61 ) 2 ]·50H 2 O [11] and K 15 H 3 -[Eu 3 (H 2 O) 3 [12] have been reported. In connection with the discovery of the anti-HIV [13,14] There are still only a few crystal structure analyses of lanthanide-containing polyoxomolybdates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Lanthanide-containing polyoxometalates constitute a type of compound of great impact. [9] Structural studies of lanthanide polyoxotungstates have been investigated and a number of compounds, for example Na 6 H 2 [Ce(W 5 O 18 ) 2 ]· 30H 2 O, [10] K 16 [Ce(P 2 W 17 O 61 ) 2 ]·50H 2 O [11] and K 15 H 3 -[Eu 3 (H 2 O) 3 [12] have been reported. In connection with the discovery of the anti-HIV [13,14] There are still only a few crystal structure analyses of lanthanide-containing polyoxomolybdates.…”
Section: Introductionmentioning
confidence: 99%
“…[4Ϫ7] In polyoxotungstate chemistry quite different structures have been described; the [As 12 Ce 16 76Ϫ anion is the largest anion yet known. [8] Lanthanide-containing polyoxometalates constitute a type of compound of great impact.…”
Section: Introductionmentioning
confidence: 99%
“…The emission bands of the europium β-diketonates, consisting of the 5 D0 → 7 FJ (J = 0 -4) transitions, are theoretically measured in the peaks split into 2J + 1 due to the Stark effect. 23,24 In this study, this effect was analyzed in the region of J = 0 -2 as shown in Table 2. The weak bands of the split peaks belonging to the 5 D0 → 7 FJ (J = 0,1,3,4) transitions were useful for distinguishing the europium β-diketonates in terms of the wavelength of the emission.…”
Section: Comparison Of Emissions By a Fluorescence Spectrometer And Tmentioning
confidence: 99%
“…(NH4)12 H2 [Eu4 (MOO4) (H20)16 (M07024)4] • 13H20 Naruke, Ozeki & Yamase, 1991), K15H3 [Eu3(H20)3(SbW9033)(W5OI8)3].25.5H20 (Yamase, Naruke & Sasaki, 1990) and Na9 [EuW10036].-32H20 (Sugeta & Yamase, 1993). In order to understand the photoluminescence properties of polyoxometallolanthanoates in general, we investigated the photoluminescence of polyoxometallosamarates, subsequently to those of the europium compounds.…”
mentioning
confidence: 99%